G238 A Local Guideline Improves Care for Children with Neutropenia. (7th April 2014) - Fallaha, J; Millership, C; Jayatunga, R; Wandroo, F
Abstract : Aims: Neutropenia is clinically significant due to its association with serious and potentially fatal infection. The National Institute of Clinical Excellence (NICE) recently published guidelines for the management of neutropenic sepsis. No guidelines exist for managing congenital and acquired neutropenia in the absence of an oncological cause. Following a literature review and a regional survey, our secondary care trust established a neutropenia guideline in September 2012 for management of neutropenia detected as an incidental finding. This was subsequently audited. Methods: 29 patients with neutropenia defined as Absolute Neutrophil Counts (ANC) < 1.5 × 10 9 were identified from coding between October 2011 and January 2013. Data was retrospectively analysed from patient records, to determine if the management of these patients improved following the introduction of the local guideline. Whether patients had timely tests, open access, secondary investigations (if applicable) and referral to local/tertiary centre for further management was assessed including the final diagnosis/outcome. Results: The majority of patients (76%) had mild to moderate (ANC >0.5 × 10 9 /l) neutropenia of whom 77% had their counts repeated in 4 weeks. 86% of patients with severe neutropenia (ANC <0.5 × 10 9 /l) had their counts repeated after 1 week as stipulated in the guideline. Both improved to 100% after introduction of the guideline. Open access for patients with ANC <0.5 × 10 9 /l were created in 42% of patients, improving to 60% post guideline. Referral to the local Haematology clinic was 100% and secondary investigations were sent in 85% of patients whose ANC remained low at 6–8 weeks. Referral to a tertiary centre for low ANC at 3 months was made only in 50%. Over half of the patients (56%) had transient/resolving neutropenia, with 15% having an autoimmune cause. Conclusion: Although the majority had only transient neutropenia, it is important that children with persistent neutropenia are appropriately managed. This can be improved by compliance with a local guideline ensuring that secondary investigations and referral to tertiary care centres are appropriately organised. For severely neutropenic children management can be improved by issuing open access so that care is delivered promptly should they become unwell. References: National Institute for Health and Care Excellence. Neutropenic sepsis: prevention and management of neutropenic sepsis in cancer patients. CG151. London: National Institute for Health and Care Excellence. Sep 2012